2016
DOI: 10.5194/acp-16-6495-2016
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous ice nucleation of viscous secondary organic aerosol produced from ozonolysis of <i>α</i>-pinene

Abstract: Abstract. There are strong indications that particles containing secondary organic aerosol (SOA) exhibit amorphous solid or semi-solid phase states in the atmosphere. This may facilitate heterogeneous ice nucleation and thus influence cloud properties. However, experimental ice nucleation studies of biogenic SOA are scarce. Here, we investigated the ice nucleation ability of viscous SOA particles. The SOA particles were produced from the ozone initiated oxidation of α-pinene in an aerosol chamber at temperatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 55 publications
5
87
0
Order By: Relevance
“…In addition to the different particle generation procedures, the resulting particle sizes vary, too, which certainly alters the ice nucleation capability (larger particles provide a larger surface area and are more likely to form ice). The findings of the above-mentioned studies can be summarized as follows: Wang et al (2012) and Ignatius et al (2016) found that atmospheric SOA particles are potentially important for ice nucleation due to their semi-solid or solid phase states by investigating SOA from naphthalene and α-pinene, respectively, whereas Ladino et al (2014) and Wagner et al (2017) found that α-pinene SOA at first is an inefficient INP at cirrus temperatures, but after precooling of the SOA particles, ice nucleation ability is increased. Schill et al (2014) found that semi-solid or glassy SOA from aqueous processing of methylglyoxal with methylamine is a poor depositional INP; however, Wilson et al (2012) found other aqueous glassy aerosol to nucleate ice heterogeneously at temperatures relevant for cirrus formation in the tropical tropopause layer.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the different particle generation procedures, the resulting particle sizes vary, too, which certainly alters the ice nucleation capability (larger particles provide a larger surface area and are more likely to form ice). The findings of the above-mentioned studies can be summarized as follows: Wang et al (2012) and Ignatius et al (2016) found that atmospheric SOA particles are potentially important for ice nucleation due to their semi-solid or solid phase states by investigating SOA from naphthalene and α-pinene, respectively, whereas Ladino et al (2014) and Wagner et al (2017) found that α-pinene SOA at first is an inefficient INP at cirrus temperatures, but after precooling of the SOA particles, ice nucleation ability is increased. Schill et al (2014) found that semi-solid or glassy SOA from aqueous processing of methylglyoxal with methylamine is a poor depositional INP; however, Wilson et al (2012) found other aqueous glassy aerosol to nucleate ice heterogeneously at temperatures relevant for cirrus formation in the tropical tropopause layer.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, no bounce measurements with pure α-pinene were performed; however, several studies (e.g. Saukko et al, 2012a;Pajunoja et al, 2015;Ignatius et al, 2016) have shown that α-pinene SOA is semisolid under the conditions relevant here.…”
Section: Particle Bounce Measurementsmentioning
confidence: 99%
See 3 more Smart Citations